POLITICAL CULTURE PATTERNS AND ALTERNATIVES FOR ELECTION DISPUTE RESOLUTION FROM ADR PERSPECTIVE (INTERNATIONAL SEMINAR, 2023)
Political culture is the view held by people's attitude patterns which are reflected in their views on political issues and political events. General elections (elections) are a real manifestation of the democratic system. Elections can be considered part of political culture because they reflect the way people participate in the political process and the expression of their political values. However, the process of holding elections does not always run smoothly, with various obstacles that can arise both during and before the election. These obstacles are problems that can have a significant impact if not addressed immediately. Election disputes arise due to problems that arise during the implementation of general elections, including dissatisfaction with the decisions of election management institutions or violations of law and administrative procedures that have the potential to influence election results. Resolving election disputes is crucial in ensuring election justice or electoral justice. Parties participating in election disputes have alternative dispute resolution, which is often informal. This research aims to explore political culture and alternative resolution of election disputes. This research applies an applied approach using qualitative methods, and data collection techniques are carried out through literature study. Thus, it is hoped that this research can provide a deeper understanding of political culture and the effectiveness of alternative dispute resolution in general election situations.